The identity of papal soldiers in the early modern age - Brunelli, Giampiero (Verbum – Analecta Neolatina, 2018)
The disproportion between the continuous attention to the military orders by the popes of the early modern age and the meager results obtained is evident. However, these were not imposed by the religious foundations of the State of the Church. The pope’s army never worked effectively because it failed to build a peculiar identity for those who militated within it. By resorting to sociology, this paper traces the mechanisms of identity building and shows the cultural proposal of a “Soldier of the Holy Church”, with repercussions in military legislation and even in the history of art. This proposal was only partly accepted, as documents indicate. In fact, it had to coexist with other forms of identity, already internalized by officers and soldiers, based on other values. Ultimately, this conflict of identity was the real cause of the weakness of the pope’s army.